Rock-magnetic and paleomagnetic survey on dated lava flows erupted during the Bruhnes and Matuyama chrons: the Mascota Volcanic Field revisited (Western Mexico) - García-Ruiz, Rafael; Goguitchaichvili, Avto; Cervantes-Solano, Miguel; Morales, Juan; Maciel-Peña, Rafael; Rosas-Elguera, José; Cejudo-Ruiz, Ruben; Urrutia-Fucugauchi, Jaime (Studia Geophysica et Geodaetica)
a1_A rock magnetic and paleomagnetic investigation was performed on some selected, radiometrically dated lava flows from the Mascota Volcanic Field (MVF), western Trans- Mexican Volcanic Belt. A set of rock-magnetic experiments and standard paleomagnetic analysis were carried out on 19 sites spanning the time interval from 2268 to 72 kyr. The paleomagnetic directions are anchored to absolute radiometric ages while no such information was available in previous studies. This makes possible to correctly evaluate the fluctuation of Earth’s magnetic field from Pliocene to Pleistocene and reveal the firm evidence of possible Levantine excursion. Both Ti-poor and Ti-rich titanomagnetites seem to carry the remanent magnetization with Curie temperatures ranging from 350°C to 537°C. Thirteen flows correspond to the Brunhes chron, one of them exhibits transitional directions, while the remaining six sites belong to the Matuyama chron. New and existing dataset for MVF were used to estimate the paleosecular variation parameters. The selected data include 35 Plio-Quaternary lava flows. After excluding the poor quality data, as well as the transitional directions, the mean paleodeclination is 356.1° and oaleoinclination 39.9°, which agree well with the geocentric axial dipole (GAD) and the expected paleodirections for the Plio-Pleistocene, as derived from the reference poles for the stable North America. The corresponding mean paleomagnetic poles are paleolongitude 226.7° and paleolatitude 86.0°. The virtual geomagnetic pole scatter for the MVF is 15.2°, which is consistent with the value expected from model G at latitude of 20° (this model provides an interpretation of the paleosecular variation at different latitudes for the time of interest). The combined paleomagnetic data, supported by positive reversal test, indicate no paleomagnetically detectable vertical-axis rotations in the study area. a2_The evidence of one transitional directions was detected, which may correspond to the Levantine excursion (360-370 kyr) or ...